Incidence of Early Adverse Events Following Medial Patellofemoral Ligament Reconstruction - Yalcin, Sercan; Seals, Karrington; Farrow, Lutul D. (The Journal of Knee Surgery, 2024)
The current literature lacks data regarding perioperative complications after medial patellofemoral ligament reconstruction (MPFLr). The objective of this study was to identify the incidence and predictors of adverse events in the first 90 days after MPFLr. Patients undergoing primary MPFLr between January 1, 2010, and December 31, 2019, were included. Predictors of readmission for any reason were identified using a multivariable logistic regression analysis. A total of 140 MPFLrs were included in the final analysis. Of these, 17 patients (12.1%) were admitted in the first 90 days after MPFLr. The most common reason for readmission was pain (7/140, 5%), followed by cellulitis (5/140, 3.5%). The only major complication was pulmonary embolism experienced by one patient (1/140, 0.7%). Univariate logistic regression analysis demonstrated that patients who ever smoked were 4.5 times (p = 0.005) more likely to be readmitted in the first 90 days. Although additional soft-tissue procedures increased the readmission rated by 21% (p = 0.810) and additional chondral procedure increased by 35% (p = 0.568), the multivariable analysis did not reveal a significant difference. Surgeons can use this information to counsel patients on what to expect following MPFLr.
Keywords: medial patellofemoral ligament reconstruction; patellofemoral instability; perioperative complication; readmission; MPFLR